The Dao Companion to Japanese Buddhist Philosophy - Kopf, Gereon (Dao Companions to Chinese Philosophy, 2019)
Content Table and Authors -- Introduction -- A: Basic Issues in Japanese Buddhist Philosophy -- Chapter 1: “Japanese Buddhism” or “Buddhism in Japan -- The Category “Japanese Buddhism”; Richard Payne -- Is There Such a Thing as Buddhist Philosophy in Japan? John Maraldo -- Buddhist Philosophy; Makio Takemura, translator: Eiji Suhara -- The Role of Women in Japanese Buddhist Philosophy; Michiko Yusa -- Buddhist Theory and Culture in Japan; Rein Raud -- Chapter 2: Current Issues in Japanese Buddhist Philosophy -- The Reception of Buddhist Thought by Contemporary Philosophers in Japan; Ralf Mueller -- Interaction Between Japanese Buddhist Philosophy and Confucianism; Tomomi Asakura -- The Philosophy Underlying Buddhist Art; Pamela Winfield -- Violence and Salvation in Buddhism; Manabu Watanabe -- Buddhist Socialist Thought in Modern Japan; James Shields -- B: Individual Thinkers -- Chapter 3: Japanese Buddhist Philosophy Before the Meiji Period -- Saichō; Victor Forte -- Kūkai; David Gardiner -- Jōkei; Jay Ford -- Hōnen; Mark Blum -- Dōgen; Steven Heine -- Keizan; Shudō Ishii, translator: Ching-yuen Cheung -- Shinran; Dennis Hirota -- Nichiren; Ruben Habito -- Chūgan Engetsu; Steffen Doell -- Takuan Sōhō; Dennis Lishka -- Hakuin Ekaku; Juhn Ahn -- Bankei Yōtaku; Enshō Kobayashi, translator: Thomas Kirchner -- Chapter 4: Japanese Buddhist Philosophy After the Meiji Period -- Nakamura Hajime; Toshi’ichi Endō -- Inoue Enryō; Rainer Schulzer -- Nishida Kitarō; Mayuko Uehara, translator: John Krummel -- Nishitani Keiji; John Krummel -- D. T. Suzuki; Michiko Yusa -- Kiyozawa Manshi; Robert Rhodes -- Tamaki Koshirō; Makio Takemura, translator: John Krummel -- Hisamatsu; Andre van Braakt -- Ueda Shizuteru; Brett Davis -- Hiratsuka Raichō; Saeko Kimura